Complete genome sequence of a mite-associated virus obtained by high-throughput sequencing analysis of an apple leaf sample - Koloniuk, Igor; Přibylová, Jaroslava; Špak, Josef (Archives of virology, 2020)
We provide the complete sequence of a virus tentatively named "Tetranychus urticae-associated picorna-like virus 1PK13" (TuaPV1-PK13) obtained from the high-throughput sequencing of a symptomless apple leaf sample. Although the virus sequence was originally derived from apple leaves, the data suggest that the virus is associated with the two-spotted mite Tetranychus urticae.
Keywords: sekvenování celého genomu; vysoce účinné nukleotidové sekvenování; Whole Genome Sequencing; Plant Leaves; Tetranychidae; zvířata; Malus; High-Throughput Nucleotide Sequencing; listy rostlin; Picornaviridae; Animals